Identiti Cina Muslim di Malaysia persempadanan perundingan & kacukan budaya - Hew, Wai Weng (Penerbit Universiti Kebangsaan Malaysia, 2014)
On ethnic identity and cultural assimilation of Chinese Muslim community in Malaysia.